Testing of resveratrol microemulsion photostability and protective effect against UV induced oxidative stress - Juškaitė Vaida; Ramanauskienė Kristina; Briedis Vitalis (Acta Pharmaceutica)
Resveratrol is well known for its antioxidant activity and susceptibility to ultraviolet radiation. Development of formulations providing improved stability and relevant drug delivery of resveratrol is still a challenging task. The aim of this study was to determine protective characteristics of formulated microemulsions by evaluating photoisomerization of resveratrol and to investigate the effects of resveratrol on human keratinocyte cells under oxidative stress caused by ultraviolet radiation. Incorporation of resveratrol into microemulsions resulted in increased photostability of active compounds and the results demonstrated that photodegradation of resveratrol was significantly delayed. Results of biopharmaceutical evaluation in vitro demonstrated that up to 60 % of resveratrol was released from microemulsions within 6 hours under a constant release rate profile. In vivo biological testing confirmed the ability of resveratrol to protect cells from oxidative stress and to increase cell viability. It was concluded that microemulsions might be considered in the development of UV light sensitive compounds.